Detection and characterization of meat adulteration in various types of meat products by using a high-efficiency multiplex polymerase chain reaction technique - Yang, Caijiao; Zhong, Guowei; Zhou, Song; Guo, Yingqi; Pan, Daodong; Wang, Sha; Liu, Qianqian; Xia, Qiang; Cai, Zhendong (Frontiers in Nutrition, 2022)
Identification of meat authenticity is a matter of increasing concerns due to religious, economical, legal, and public health reasons. However, little is known about the inspection of eight meat species in one tube reaction due to technological challenge of multiplex polymerase chain reaction (PCR) techniques. Here, a developed multiplex PCR method can simultaneously authenticate eight meat species including ostrich (753 bp), cat (564 bp), goose (391 bp), duck (347 bp), chicken (268 bp), horse (227 bp), dog (190 bp), and sheep (131 bp). The detectable deoxyribonucleic acid (DNA) contents for each target species was as low as 0.01 ng in both raw and heat-treated meat or target meat down to 0.1% (w/w) of total meat weight reflecting high stability of the assay in heat processing condition, indicating that this method is adequate for tracing meat origin in real-world meat products, which has been further validated by authenticity assays of commercial meat products. Overall, this method is a powerful tool for accurate evaluation of meat origin with a good application foreground.